+0  
 
+3
372
6
avatar

 

In a triangle ABC, a, b , c are the opposite side of angle A,angle B ,and angle C, and  $${\frac{{\mathtt{cosB}}}{{\mathtt{cosc}}}} = {\mathtt{\,-\,}}{\frac{{\mathtt{b}}}{\left({\mathtt{2}}{\mathtt{\,\times\,}}{\mathtt{a}}{\mathtt{\,\small\textbf+\,}}{\mathtt{c}}\right)}}$$

(I)find the angle B

(2)if b=square root 13 ,and a+c=4 what is the area of the triangle ABC

Guest Feb 9, 2015

Best Answer 

 #1
avatar+26750 
+13

 Angle B

.

Alan  Feb 9, 2015
 #1
avatar+26750 
+13
Best Answer

 Angle B

.

Alan  Feb 9, 2015
 #2
avatar+87294 
+5

Very impressive, Alan....!!!

 

CPhill  Feb 9, 2015
 #3
avatar+92775 
0

Yes, nice work, thank you :)))

Melody  Feb 9, 2015
 #4
avatar+19620 
+10

In a triangle ABC, a, b , c are the opposite side of angle A,angle B ,and angle C, and

 $${\frac{{\mathtt{cosB}}}{{\mathtt{cosc}}}} = {\mathtt{\,-\,}}{\frac{{\mathtt{b}}}{\left({\mathtt{2}}{\mathtt{\,\times\,}}{\mathtt{a}}{\mathtt{\,\small\textbf+\,}}{\mathtt{c}}\right)}}$$

(I) find the angle B

 

$$\boxed{ \dfrac{ \cos{(B)} }{\cos{(C)}}=-\dfrac{b}{(2a+c)} }
\small{\text{
$\quad $For any triangle:
$
a=b\cos{(C)}+c\cos{(B)}.
$
}}\\\\
\small{\text{
$
(2a+c)\cos{(B)} = -b\cos{(C)} \quad | \quad -b\cos{(C)}= c\cos{(B)} - a
$
}}\\
\small{\text{
$
(2a+c)\cos{(B)} = c\cos{(B)} - a
$
}}\\
\small{\text{
$
(2a)\cos{(B)} = - a
$
}}\\
\small{\text{
$
2\cos{(B)} = - 1
$
}}\\
\small{\text{
$
\textcolor[rgb]{1,0,0}{\cos{(B)} = - \dfrac{1}{2} \qquad B = 120\ensurement{^{\circ}}
}$
}}$$

heureka  Feb 10, 2015
 #5
avatar+19620 
+8

(2) if b=square root 13 ,and a+c=4 what is the area of the triangle ABC

$$\boxed{\small{\text{(1) The shape of the triangle by Heron's formula:$\quad A^2=s(s-a)(s-b)(s-c) \quad s = \frac{a+b+c}{2}$
}} }\\\\
\small{\text{$s =\frac{a+c+b}{2} \quad | \quad a+c=4
$
}}\\
\small{\text{
$s = \frac{4+b}{2} = 2 + \frac{b}{2}\qquad
\boxed{s=2 + \frac{b}{2}
} $
}}\\\\
\small{\text{
$
A^2=s(s-a)(s-b)(s-c) = \textcolor[rgb]{1,0,0}{s(s-b)} (s-a)(s-c) $
}}
}}\\
\small{\text{
$
\textcolor[rgb]{1,0,0}{s(s-b)}=( 2+\frac{b}{2} )(2+\frac{b}{2}-b) =(2+\frac{b}{2})(2-\frac{b}{2})=4-\frac{b^2}{4} \quad | \quad b^2=13
$
}}\\
\small{\text{
$
\textcolor[rgb]{1,0,0}{s(s-b)} = 4-\frac{13}{4} =\frac{16-13}{4} = \frac{3}{4}$
}}\\\\
\small{\text{
$
A^2=\textcolor[rgb]{1,0,0}{s(s-b)} (s-a)(s-c) = \textcolor[rgb]{1,0,0}{ \frac{3}{4} } (s-a)(s-c) $
}}\\
\small{\text{
$
A^2=\frac{3}{4}(s-a)(s-c)= \frac{3}{4}(s^2-sc-sa+ac)
=\frac{3}{4}(s^2-s(a+c)+ac) \quad | \quad a+c=4
$
}}\\
\small{\text{
$
A^2=\frac{3}{4}( \textcolor[rgb]{1,0,0}{s^2-4s} +ac)$
}}\\
\small{\text{
$
\textcolor[rgb]{1,0,0}{s^2-4s} = (2+ \frac{b}{2} )^2-4(2+\frac{b}{2}
)=4+2b+ \frac{b^2}{4} -8-2b=-4+\frac{b^2}{4} =\frac{-16+13}{4}= -\frac{3}{4}
$
}}\\\\
\small{\text{
$
A^2=\frac{3}{4}( \textcolor[rgb]{1,0,0}{ -\frac{3}{4}
} +ac) $
}}\\
\small{\text{
$
A^2*\frac{4}{3} -ac + \frac{3}{4} = 0$
}}\\$$

$$\boxed{\small{\text{(2) The shape of the triangle :$\quad
A= \dfrac {ac \sin{(B)} } {2} \qquad ac = \dfrac{2A}{\sin{(B)}}
$
}} }\\\\
\small{\text{
$
A^2*\frac{4}{3} -ac + \frac{3}{4} = 0$
}} }\\
\small{\text{
$
A^2*\frac{4}{3} -\frac{2A}{\sin{(B)}} + \frac{3}{4} = 0$
}} }\\\\
\small{\text{
$
A_{1,2}=
\dfrac
{
\frac{2}{\sin{(B)}}
\pm\sqrt{
\left( \frac{2}{ \sin{(B)} } \right)^2-4*\frac{4}{3}*(\frac{3}{4} ) }
}
{ 2*\frac{4}{3} }
=
\dfrac
{
\frac{2}{\sin{(B)}}
\pm 2\sqrt{
\frac{1}{ \sin^2{(B)} }-1 }
}
{ \frac{8}{3} }
=
\dfrac
{
\frac{2}{\sin{(B)}}
\pm 2 \frac{ \cos{(B)} } { \sin{(B)} } }
{ \frac{8}{3} }
$
}}\\
\small{\text{
$
A_{1,2}
=
\frac{3}{4}
\left(
\frac{1}{\sin{(B)}}
\pm \frac{ \cos{(B)} } { \sin{(B)} }
\right)
=
\frac{3}{4}
\left(
\frac{1\pm\cos{(B)} }{\sin{(B)}}
\right)
$
}}\\\\
\small{\text{
$
A_{1}
=
\frac{3}{4}
\left(
\frac{1+\cos{(B)} }{\sin{(B)}}
\right)
\quad | \quad \cos{(B)} = - \frac{1}{2} \quad \sin{(B)} =\sqrt{ 1-\cos^2{ (B) }} = \frac{\sqrt{3}}{2}
$
}}\\
\small{\text{
$
A_{1}=\frac{3}{4}*\frac{1+ (-\frac{1}{2}) }{ \frac{\sqrt{3}}{2} }
=\frac{3}{4}*\frac{2}{ \sqrt{3} } *\frac{1}{2}
=\frac{3}{4}*\frac{2*\sqrt{3}}{3} *\frac{1}{2}
= \frac{1}{4}*\sqrt{3}
$
}}\\
\small{\text{
$
\boxed{A_{1}= \frac{1}{4}\sqrt{3} $ no solution!$}
$
}}\\\\
\small{\text{
$
A_{2}
=
\frac{3}{4}
\left(
\frac{1-\cos{(B)} }{\sin{(B)}}
\right)
\quad | \quad \cos{(B)} = - \frac{1}{2} \quad \sin{(B)} =\sqrt{ 1-\cos^2{ (B) }} = \frac{\sqrt{3}}{2}
$
}}\\
\small{\text{
$
A_{2}=\frac{3}{4}*\frac{1- (-\frac{1}{2}) }{ \frac{\sqrt{3}}{2} }
=\frac{3}{4}*\frac{2}{ \sqrt{3} }*\frac{3}{2}
=\frac{3}{4}* \frac{2*\sqrt{3}}{3} *\frac{3}{2}
= \frac{3}{4}*\sqrt{3}
$
}}\\
\small{\text{
$
\boxed{A_{2}= \frac{3}{4}\sqrt{3}}
$
}}$$

heureka  Feb 10, 2015
 #6
avatar+19620 
+8

   $$\small{\text{
c and a ?
$
\boxed{
\; ac = \dfrac{2A}{\sin{(B)}} \qquad a=4-c \qquad A= \frac{3}{4}\sqrt{3} \qquad \sin{(B)}=\frac{\sqrt{3}}{2}\;
}
$
}}\\\\\\
\small{\text{
$
(4-c)c = 2*\dfrac{3\sqrt{3}}{4}*\dfrac{2}{\sqrt{3}}= 3$
}}\\\\
\small{\text{
$
c^2-4c+ 3 =0 \qquad
$
}}
\small{\text{
$
c_{1,2}=\dfrac{
4\pm\sqrt{16-4*3 }
}
{2}
= \dfrac{ 4\pm \sqrt{4} } {2}
= \dfrac{ 4\pm 2 } {2}
=2\pm 1
$
}}\\\\
\small{\text{
$
c_1= 2+1 \quad \boxed{c_1=3} \qquad c_2= 2-1 \quad \boxed{c_2= 1}$
}}\\\\
\small{\text{
$
a_1=4-c_1 \qquad a_1=4-3 \qquad \boxed{a_1=1}$
}}\\
\small{\text{
$
a_2=4-c_2 \qquad a_2= 4-1 \qquad \boxed{a_2=3}$
}}$$

heureka  Feb 10, 2015

13 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.